Estudio de las mutaciones en el gen de Telomerasa transcriptasa inversa (TERT) y su valor pronóstico en gliomas - Moggia, Daniela (2023)
IDH (isocitrate dehydrogenase) gene mutations are present in the majority of low-grade diffuse gliomas and define the clinicopathological nucleus of the respective morphologically defined entities. On the contrary, according to the WHO classification of 2016, the majority of glioblastomas belong to the category IDH-wild (wildtype), which is defined by exclusion. TERT gene mutations (telomerase reverse transcriptase gene) have been suggested as a molecular marker for primary glioblastomas. We analyzed the molecular, histopathological and clinical profiles of a series of 17 diffuse gliomas (WHO grades II-IV) diagnosed and operated in the Sanatorium Anchorena, in which an analysis of TERT gene promoter mutations was performed as part of a research study in the Department of Genetics of the Hospital de Clínicas, CABA, Argentina. The tumors had already been sequenced to assess the status of the IDH1 gene and that information was available.\nMutations in the TERT gene promoter were present in 41% of the tumors (7 of the total of 17) and in 42% of the cases carrying the wild-type (wt) IDH1 gene (5 of 12). It was observed that all patients (except two) who carried mutations in the TERT gene had the wild-type IDH1 gene. Therefore, we can say that the mutations in the TERT gene promoter are inversely correlated with the mutations observed in the IDH1 gene which is a known molecular factor for a favorable prognosis. In 53% of cases (9 of the 17), a T> C polymorphism was identified in the TERT promoter at the -245 bp position (with respect to the ATG initiation codon) that could have an influence on glioma evolution . It was observed that mutations in the TERT gene promoter are correlated with grade IV glioma (4 patients with grade IV and 2 patients with grade II and III, not counting San). It was also found that mutations in the TERT gene promoter correlates with tumor growth and patient death. Thus it was seen that 4 of the 6 patients with mutations in the TERT promoter experienced tumor growth and / or death. It is concluded that mutations in the TERT gene promoter are molecular markers to take into account along with other biological changes to know the evolution of the tumor and the patient's life prognosis.